Phenotype and genotype in 52 patients with Rubinstein–Taybi syndrome caused by EP300 mutations. Issue 12 (20th September 2016) - Fergelot, Patricia; Van Belzen, Martine; Van Gils, Julien; Afenjar, Alexandra; Armour, Christine M.; Arveiler, Benoit; Beets, Lex; Burglen, Lydie; Busa, Tiffany; Collet, Marie; Deforges, Julie; de Vries, Bert B. A.; et al.
Abstract : Rubinstein–Taybi syndrome (RSTS) is a developmental disorder characterized by a typical face and distal limbs abnormalities, intellectual disability, and a vast number of other features. Two genes are known to cause RSTS, CREBBP in 60% and EP300 in 8–10% of clinically diagnosed cases. Both paralogs act in chromatin remodeling and encode for transcriptional co‐activators interacting with >400 proteins. Up to now 26 individuals with an EP300 mutation have been published. Here, we describe the phenotype and genotype of 42 unpublished RSTS patients carrying EP300 mutations and intragenic deletions and offer an update on another 10 patients. We compare the data to 308 individuals with CREBBP mutations. We demonstrate that EP300 mutations cause a phenotype that typically resembles the classical RSTS phenotype due to CREBBP mutations to a great extent, although most facial signs are less marked with the exception of a low‐hanging columella. The limb anomalies are more similar to those in CREBBP mutated individuals except for angulation of thumbs and halluces which is very uncommon in EP300 mutated individuals. The intellectual disability is variable but typically less marked whereas the microcephaly is more common. All types of mutations occur but truncating mutations and small rearrangements are most common (86%). Missense mutations in the HAT domain are associated with a classical RSTS phenotype but otherwise no genotype–phenotype correlation is detected. Pre‐eclampsia occurs in 12/52 mothers of EP300 mutated individuals versus in 2/59 mothers of CREBBP mutated individuals, making pregnancy with an EP300 mutated fetus the strongest known predictor for pre‐eclampsia. © 2016 Wiley Periodicals, Inc.